2020
DOI: 10.1109/access.2020.2994277
|View full text |Cite
|
Sign up to set email alerts
|

Ultra Reliable Communication via Optimum Power Allocation for HARQ Retransmission Schemes

Abstract: In this work, we develop low complexity, optimal power allocation algorithms that would allow ultra reliable operation at any outage probability target with minimum power consumption in the finite blocklength regime by utilizing Karush-Kuhn-Tucker (KKT) conditions. In our setup, we assume that the transmitter does not know the channel state information (CSI). First, we show that achieving a very low packet outage probability by using an open loop setup requires extremely high power consumption. Thus, we resort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…The solution showed that EBP model with retransmission is an ultra-reliable power saving scheme which improves the energy efficiency with limited increase in latency. Better performance and higher EEE gain could be achieved by applying Chase Combining (CC-HARQ) and Incremental redundancy (IR-HARQ) protocols [39]. This is left as possible extension for this work along with the analysis of EEE in multi-user networks as in Fig.…”
Section: Discussionmentioning
confidence: 96%
“…The solution showed that EBP model with retransmission is an ultra-reliable power saving scheme which improves the energy efficiency with limited increase in latency. Better performance and higher EEE gain could be achieved by applying Chase Combining (CC-HARQ) and Incremental redundancy (IR-HARQ) protocols [39]. This is left as possible extension for this work along with the analysis of EEE in multi-user networks as in Fig.…”
Section: Discussionmentioning
confidence: 96%
“…where R is the code-rate, whereas R c is the rate achieved after th round, also termed as effective rate. Outage probability is also measured through various other parameters such as signal to interference plus noise ratio (SINR) [123], [124], [127] and accumulated mutual information (AMI) [125], [126]. Outage probability is also related to the achieved transmission rate.…”
Section: B Reliabilitymentioning
confidence: 99%
“…It is therefore necessary to find optimal power allocations for a system to get rid of maximum possible hinges. Optimal average power allocation for URLLC is derived in [127] and given as,…”
Section: Energy and Power Efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, hybrid ARQ (HARQ) combines error detection with error correction by adding redundancy bits to the transmitted frames, and if the message decoding fails, a series of retransmission rounds are performed [5][6][7][8]. Depending on whether the erroneous message is discarded or stored, the HARQ is categorized as Type I HARQ or soft combining HARQ, respectively [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%